Antiatherogenic Potential of Extracts from the Gray Oyster Medicinal Mushroom, Pleurotus pulmonarius (Agaricomycetes), In Vitro - Abidin, Mohamad Hamdi Zainal; Abdullah, Noorlidah; Abidin, Nurhayati Zainal (Begell House, 2018)
This study evaluates the in vitro inhibition of angiotensin-converting enzyme (ACE) and 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMG-CoA) by Pleurotus pulmonarius extracts. The protective effect on the endothelial membrane against oxidative stress through the protection of nitric oxide bioavailability, as well as inhibition of endocan expression, was evaluated using human aortic endothelial cells (HAECs). Crude cold aqueous extract exhibited the most potent inhibitory activities against ACE and HMG-CoA reductase, with 61.79% and 44.30% inhibition, respectively. It also protected the bioavailability of NO released by HAECs, with 84.88% cell viability. The crude hot water extract was the most potent in inhibiting endocan expression, with 18.61% inhibition.